Self-Expanding Metal Stent (SEMS): an innovative rescue therapy for refractory acute variceal bleeding - Changela, Kinesh; Ona, Mel A.; Anand, Sury; Duddempudi, Sushil (Endoscopy International Open, 2014)
Background: Acute variceal bleeding (AVB) is a life-threatening complication of liver cirrhosis or less commonly splenic vein thrombosis. Pharmacological and endoscopic interventions are cornerstones in the management of variceal bleeding but may fail in 10 – 15 % of patients. Rescue therapy with balloon tamponade (BT) or transjugular intrahepatic portosystemic shunt (TIPS) may be required to control refractory acute variceal bleeding effectively but with some limitations. The self-expanding metal stent (SEMS) is a covered, removable tool that can be deployed in the lower esophagus under endoscopic guidance as a rescue therapy to achieve hemostasis for refractory AVB.Aims: To evaluate the technical feasibility, efficacy, and safety of SEMS as a rescue therapy for AVB.Methods: In this review article, we have performed an extensive literature search summarizing case reports and case series describing SEMS as a rescue therapy for AVB. Indications, features, technique, deployment, success rate, limitations, and complications are discussed.Results: At present, 103 cases have been described in the literature. Studies have reported 97.08 % technical success rates in deployment of SEMS. Most of the stents were intact for 4 – 14 days with no major complications reported. Stent extraction had a success rate of 100 %. Successful hemostasis was achieved in 96 % of cases with only 3.12 % found to have rebleeding after placement of SEMS. Stent migration, which was the most common complication, was observed in 21 % of patients.Conclusion: SEMS is a safe and effective alternative approach as a rescue therapy for refractory AVB.